2000
DOI: 10.1149/1.1394075
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: “Corrosion Properties of Electroplated CoBiFe Films” [J. Electrochem. Soc., 146, 1845 (1999)]

Abstract: In the paragraph subtitled "Crystal structure.-Effect of saccharin" the first sentence should read:Figures 4 to 7 show micrographs of TEM images and THEED patterns of CoNiFe films in which the compositions are near the phase boundary between fcc and body-centered cubic (bcc) structures. 14 ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 13.66.222.141 Downloaded on 2019-04-04 to IP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…As a CoFe based ternary alloy, FeCoNi alloy is a widely investigated magnetic material [1,2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Osaka group studied magnetic properties and other physical properties of electrodeposited FeCoNi alloys [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a CoFe based ternary alloy, FeCoNi alloy is a widely investigated magnetic material [1,2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Osaka group studied magnetic properties and other physical properties of electrodeposited FeCoNi alloys [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Osaka group studied magnetic properties and other physical properties of electrodeposited FeCoNi alloys [16][17][18][19][20][21][22]. Magnetic moments as high as 2.1 T were achieved at a composition of 12Ni65Co23Fe with a coercivity of 1.2 Oe [19].…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al [47] studied the corrosion performance of nanocrystalline Co 65 Ni 12 Fe 23 ternary alloys (grain sizes 10-40 nm) in deaerated 2.5 wt % NaCl solution. Potentiodynamic polarization curves showed that the material passivated in this solution with passivation current densities of $30 mA/cm 2 .…”
Section: E2 Nanocrystalline Cobalt and Cobalt Alloysmentioning
confidence: 99%
“…While this permits to influence phase formation and grain size, it may negatively affect the corrosion properties. 176 By careful optimization of deposition parameters nanocrystalline ternary alloys with a grain size on the order of 10 nm were produced that exhibited saturation values of 2 Tesla or more. 21 Multilayer alloys have been an important field of research during the last 20 years.…”
Section: Electrochemical Engineering Aspects Of Electrodepositionmentioning
confidence: 99%